2021
DOI: 10.3390/en14185693
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Carbonization of Chemical and Biological Pulp Mill Sludges

Abstract: A modern pulp mill generates a variety of different by-products and waste streams, some of these can be recycled, refined, sold, or used on-site for energy production. However, some, such as chemical and biological sludges produced in wastewater treatment cannot be reused or disposed of easily, mainly due to their high moisture content and poor drying characteristics. Tightening legislation regarding waste disposal as well as the growing need to increase the process efficiencies of pulp mills act as driving fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…non-crystalline) matter. This together with the fact that the detection limit of XRD spectrometry is normally between 1 % -2 % [23] and only the crystalline forms of cellulose fibres are able to be identified by XRD were reasons why the presence of cellulose was not observed in our sludge, although it is a common material in pulp and paper mill sludges [24].…”
Section: Minerals In the Sludge And Sludge Ashmentioning
confidence: 90%
See 1 more Smart Citation
“…non-crystalline) matter. This together with the fact that the detection limit of XRD spectrometry is normally between 1 % -2 % [23] and only the crystalline forms of cellulose fibres are able to be identified by XRD were reasons why the presence of cellulose was not observed in our sludge, although it is a common material in pulp and paper mill sludges [24].…”
Section: Minerals In the Sludge And Sludge Ashmentioning
confidence: 90%
“…The poor drying characteristic of the sludge is due to its the gel-like structure consisting largely of extra-cellular polymeric substances and high interstitial water, i.e. water stored within the sludge flocs by capillary forces and chemically bound intracellular water [24]. This indicates that the incineration of this residue as such will lead to an uneconomical energy balance when combusted in biomass boilers.…”
Section: Physical and Chemical Properties Of The Sludge And Sludge Ashmentioning
confidence: 99%
“…The main disposal challenge of sludge is directly related to humidity (around 85-90% (wb)) [10]. Thus, several studies have concluded that a drying stage for sludge material is essential before final disposal [17][18][19][20], for transportation, handling, and landfilling cost reduction. Thermal drying is a commonly used method for phase separation treatment in the sludge management and reuse process when it is a co-product.…”
Section: Introductionmentioning
confidence: 99%

Solar Drying of Sludge from a Steel-Wire-Drawing Industry

Matias Gonçalves,
Mendoza-Martinez,
Alves Rocha
et al. 2023
Energies
Self Cite
“…Pulp and paper mill sludge has been utilized as a carbon precursor to produce activated biochar. This industrial sector generates large amounts of sludge residues commonly used as fuel or sent to landfills, but it could have a more sustainable use . Only in Sweden, 257 kilo tonnes of dry sludge solids are generated annually by paper and pulp mills .…”
Section: Introductionmentioning
confidence: 99%